Towards a better knot: Using mechanics methods to evaluate three knot-tying techniques in laparo-endoscopic single-site surgery - Xu, An An (J Minim Access Surg, 2015)
INTRODUCTION: Knot tying is difficult but important for laparo-endoscopic single-site surgery (LESS). There are several techniques for LESS knot-tying. However, objective assessment of these skills has not yet been established. The aim of this study was to assess three different knot-tying techniques in LESS using mechanical methods. MATERIALS AND METHODS: The subject tied 24 knots, eight knots with each of the three techniques in an inanimate box laparoscopic trainer while the movements of their instruments were evaluated using a LESS mechanical evaluation platform. The operations were assessed on the basis of the time, average load of the dominant hand. Then, forces caused the knots to rupture were measured using a material testing system and used to compare the knots's strength. RESULTS: The intracorporeal one-hand knot-tying technique presented significantly better time and average load scores than the extracorporeal knot-tying technique (P < 0.01), and the intracorporeal side winding technique was more time and average load consuming in comparison to other techniques during the performance of knot-tying (P < 0.01). The intracorporeal one-handed knot-tying knots can tolerate better distraction forces compared with the intracorporeal side winding knot-tying knots and the extracorporeal knot-tying knots (P < 0.05). CONCLUSIONS: The intracorporeal one-hand knot-tying technique and knots showed better results than the intracorporeal “side winding” technique and the extracorporeal knot-tying technique in terms of the time, average load taken and the force caused the knot to rupture.